Fluoroplastic insulating high-temperature-resistant fireproof cable and preparation method thereof
By forming an interpenetrating polymer network with functionalized ethylene-tetrafluoroethylene copolymer and vinyl-terminated polydimethylsiloxane, and utilizing microwave and infrared crosslinking reactions, the problem of poor flexibility in fluoroplastic cables was solved, and fluoroplastic cables with high flexibility and high mechanical strength were prepared.
Patent Information
- Application Number
- CN202511227615.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-29
- Publication Date
- 2025-12-05
- Estimated Expiration
- 2045-08-29
AI Technical Summary
Fluoroplastics exhibit high bending stiffness due to their rigid molecular chains and high crystallinity, which limits the flexibility of cables and makes them difficult to use in confined, complex spaces and repeated bending applications. Furthermore, existing blending methods lead to a decrease in the mechanical properties of the materials.
A fluoroplastic insulating layer was prepared by forming an interpenetrating polymer network using a functionalized ethylene-tetrafluoroethylene copolymer and vinyl-terminated polydimethylsiloxane. The two polymer networks were then induced to form using microwave and infrared crosslinking reactions respectively through an energy field gradient-responsive catalytic/crosslinking system, thus avoiding chemical interference.
This technology achieves high flexibility and high mechanical strength in fluoroplastic cables, making them easy to wire and install. At the same time, it maintains stable performance in high and low temperature environments, solving the problems of high rigidity and poor flexibility in traditional fluoroplastic cables.
Smart Images

Figure CN121075732A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of electric wire and cable, in particular to a fluoroplastic insulated high-temperature-resistant fireproof cable and a preparation method thereof. BACKGROUND
[0002] Fluoroplastics, such as ethylene-tetrafluoroethylene copolymer (ETFE) and fusible polytetrafluoroethylene (PFA), are widely used as insulation and sheath materials for special cables due to their excellent high-temperature resistance, chemical stability and electrical insulation performance, especially in harsh environments such as aerospace, petrochemical industry and nuclear industry.
[0003] However, fluoroplastic materials have strong molecular chain rigidity and high crystallinity, which results in large bending stiffness in macroscopic view. The overall flexibility of the cable using such materials as a sheath layer is limited, which brings inconvenience to the laying and installation of the cable in narrow and complex spaces, and may also affect the service life of the cable in dynamic application occasions requiring repeated bending.
[0004] In order to improve the flexibility of fluoroplastics, there are methods of physically blending them with flexible polymer materials such as organosilicon elastomers in the prior art. However, due to the differences in molecular structure, polarity and surface energy between fluoroplastics and organosilicon polymers, the two-phase materials have poor thermodynamic compatibility. This incompatibility leads to the difficulty of forming a uniform microstructure during melt blending, and the interface bonding force is weak. Finally, the internal phase interface of the blended material becomes a stress concentration point and is damaged under external force, resulting in a decrease in key mechanical properties such as tensile strength and elongation at break, which cannot meet the requirements of high-performance cable sheath. Therefore, the present application provides a fluoroplastic insulated high-temperature-resistant fireproof cable and a preparation method thereof to solve the problems existing in the prior art. SUMMARY
[0005] In view of the deficiencies of the prior art, the present application provides a fluoroplastic insulated high-temperature-resistant fireproof cable and a preparation method thereof, which solves the problems of discontinuous control trajectory, static and non-adjustable emotion mapping, lack of user feedback closed loop, weak self-adaptive ability and insufficient fusion of multi-dimensional control information in the prior art.
[0006] To achieve the above purpose, the present application realizes the following technical solutions:
[0007] The first aspect of the present application provides a fluoroplastic insulated high-temperature resistant fireproof cable, which comprises a conductor layer composed of a plurality of twisted copper wires, a fluoroplastic insulation layer surrounding the conductor layer, a shielding layer surrounding the fluoroplastic insulation layer, the shielding layer being a copper braid structure, an armor layer surrounding the shielding layer, the armor layer being woven with stainless steel wires, and a sheath layer surrounding the armor layer, the sheath layer comprising the following components in mass fractions:
[0008] functional ethylene-tetrafluoroethylene copolymer: 50-70 parts by mass;
[0009] vinyl-terminated polydimethylsiloxane: 30-50 parts by mass;
[0010] hydrogen-containing silicone oil: 1.5-3.0 parts by mass;
[0011] energy field gradient responsive synergistic catalysis / crosslinking system: 2.05-2.7 parts by mass;
[0012] fluorine-containing silane coupling agent: 0.5-2.0 parts by mass.
[0013] The functional ethylene-tetrafluoroethylene copolymer is a graft copolymer of ethylene-tetrafluoroethylene copolymer and 4-hydroxystyrene.
[0014] In another technical solution, the energy field gradient responsive synergistic catalysis / crosslinking system is composed of a microwave-sensitive platinum-gold catalyst inhibitor and an infrared-sensitive organic peroxide. The mass fraction of the microwave-sensitive platinum-gold catalyst inhibitor is 0.05-0.2 parts, and the mass fraction of the infrared-sensitive organic peroxide is 1.0-2.5 parts.
[0015] In another specific technical solution, the kinematic viscosity of the vinyl-terminated polydimethylsiloxane at 25°C is 30,000-60,000 mm 2 / s, and the vinyl content is 0.04-0.08 mmol / g.
[0016] The second aspect of the present application provides a preparation method of a fluoroplastic insulated high-temperature resistant fireproof cable, comprising the following steps:
[0017] S1, preparing a cable core: twisting a plurality of copper wires into a conductor layer; sequentially coating a fluoroplastic insulation layer, a shielding layer and an armor layer on the outer periphery of the conductor layer to obtain a cable core to be coated with a sheath; the shielding layer is formed by braiding a copper tape on the outer periphery of the fluoroplastic insulation layer, and the armor layer is formed by braiding a stainless steel wire on the outer periphery of the shielding layer;
[0018] S2, preparing jacket premix: blending and granulating functionalized ethylene-tetrafluoroethylene copolymer, end-vinyl polydimethylsiloxane, hydrogen-containing silicone oil, energy field gradient responsive synergistic catalysis / crosslinking system and fluorine-containing silane coupling agent to obtain jacket premix granules;
[0019] S3, jacket extrusion: extruding the jacket premix granules on the armor layer of the core to form an uncrosslinked jacket layer;
[0020] S4, energy field gradient crosslinking: continuously passing the cable coated with the uncrosslinked jacket layer through an energy field gradient responsive vulcanization pipeline to perform crosslinking and curing in the first zone and the second zone in sequence;
[0021] The first zone is a microwave activation zone, and a microwave field with a frequency of 2.45 GHz ± 50 MHz is applied, with a power of 20-40 kW;
[0022] The second zone is an infrared curing zone, and an infrared ray with a wavelength peak of 3-8 μm is applied, with a total radiation power of 80-120 kW.
[0023] The arrangement of step S4 realizes sequential crosslinking of two different chemical systems. In the first zone, the applied microwave field energy is selectively absorbed by the microwave-sensitive platinum catalyst inhibitor, thereby initiating the crosslinking reaction of end-vinyl polydimethylsiloxane and hydrogen-containing silicone oil to form a second polymer network. Subsequently, in the second zone, the applied infrared energy is absorbed by the infrared-sensitive organic peroxide, thereby initiating the crosslinking reaction of the functionalized ethylene-tetrafluoroethylene copolymer to form a first polymer network. This sequential crosslinking process distinguished by energy field avoids chemical interference between the two crosslinking reaction systems at the same time point, thereby generating the aforementioned interpenetrating polymer network structure in situ in the jacket layer.
[0024] In one specific embodiment, the fluoroplastic insulation layer in step S1 is a meltable polytetrafluoroethylene insulation layer formed by coating at an extrusion temperature of 390-410°C.
[0025] In one specific embodiment, the specific process for preparing the jacket premix in step S2 is: melt blending the functionalized ethylene-tetrafluoroethylene copolymer, end-vinyl polydimethylsiloxane, hydrogen-containing silicone oil and fluorine-containing silane coupling agent through a twin-screw extruder at a temperature of 110-150°C; at the end of blending, adding the energy field gradient responsive synergistic catalysis / crosslinking system through the side feeding port of the twin-screw extruder and rapidly dispersing at a temperature of 110-120°C before discharging and granulating.
[0026] In one embodiment, the process parameters for the sheath extrusion in step S3 are: 120-140℃ for the feeding zone, 140-160℃ for the compression zone, and 150-170℃ for the die head.
[0027] In one embodiment, in step S4, the cable continuously passes through the energy field gradient-responsive vulcanization pipeline at a speed of 5-15 m / min, and after leaving the pipeline, is sent into a circulating water tank with a water temperature of 20-40℃ for cooling and shaping.
[0028] The present application provides a fluoroplastic insulated high-temperature resistant fireproof cable and a preparation method.
[0029] 1. The fluoroplastic insulated high-temperature resistant fireproof cable of the present application adopts an interpenetrating polymer network structure formed in situ by functionalized ethylene-tetrafluoroethylene copolymer and organosilicon prepolymer. In this structure, the crosslinked fluoropolymer network provides excellent high-temperature resistance, chemical corrosion resistance and mechanical strength, while the physically entangled organosilicon elastomer network endows the material with excellent flexibility. This structural design realizes the synergy of the properties of the two materials at the molecular level, solving the technical problems of rigidity and poor flexibility of traditional fluoroplastic cables, and enabling the cable to be easily installed in narrow or complex spaces while maintaining high protection performance.
[0030] 2. The preparation method used in the present application realizes precise and sequential control of two different chemical crosslinking systems by setting an energy field gradient-responsive vulcanization pipeline. The microwave field in the first zone selectively activates the platinum catalyst, preferentially completing the crosslinking of the organosilicon network; the infrared radiation field in the second zone specifically initiates the decomposition of organic peroxide, completing the crosslinking of the fluoropolymer network. This non-contact and step-by-step energy input method effectively avoids the chemical interference problems such as catalyst poisoning or reaction runaway that may occur when the two reaction systems are heated simultaneously, ensuring that both polymer networks are formed completely and uniformly, thereby guaranteeing the stability and reliability of the performance of the final sheath product.
[0031] 3. The present application prepares functionalized ethylene-tetrafluoroethylene copolymer by introducing functional groups into the inert ethylene-tetrafluoroethylene copolymer molecular chain. This design provides the necessary active sites for the subsequent peroxide crosslinking reaction, significantly improving the crosslinking efficiency and crosslinking density of the fluoropolymer network. This not only ensures the effective formation of the rigid network, providing a solid performance foundation for the final material, but also makes it possible to achieve efficient crosslinking under relatively mild industrial continuous production conditions, which is of great significance to the feasibility and economy of the entire process. BRIEF DESCRIPTION OF DRAWINGS
[0032] Figure 1 The present application provides a fluoroplastic insulated high-temperature resistant fireproof cable and a preparation method. Detailed Implementation
[0033] The following is in conjunction with the appendix Figure 1 This application will be described in further detail below.
[0034] Ethylene-tetrafluoroethylene copolymer, prepared in-house according to the present invention, see Preparation Example 1;
[0035] 4-Hydroxystyrene, CAS No.: 2628-17-3;
[0036] 2,5-Dimethyl-2,5-bis(tert-butylperoxy)hexane, CAS No.: 78-63-7;
[0037] N,N-Dimethylformamide, CAS No.: 68-12-2;
[0038] Meltable polytetrafluoroethylene, CAS No.: 26655-00-5;
[0039] Microwave-sensitive inhibited platinum catalyst: CAS No.: 68478-92-2;
[0040] Fluorinated silane coupling agent (3-(heptafluoroisopropoxy)propyltriethoxysilane), CAS No.: 83048-65-1;
[0041] Infrared-sensitive organic peroxide (dicumyl peroxide, DCP), CAS No.: 80-43-3.
[0042] Preparation steps:
[0043] In a 20L stainless steel reactor equipped with a mechanical stirrer, reflux condenser, and nitrogen inlet / outlet, add 10L of N,N-dimethylformamide (DMF). Start stirring and heat the reactor to 125°C. At this temperature, slowly add 2kg of ethylene-tetrafluoroethylene copolymer (ETFE) particles, and continue stirring for 5 hours until the ETFE is completely dissolved and a homogeneous solution is formed.
[0044] The temperature of the reactor was lowered to 95°C. Under nitrogen protection, 150g of 4-hydroxystyrene (4-HBS) and 60g of potassium tert-butoxide were added to the reactor and stirred for 30 minutes to disperse them evenly.
[0045] 30 g of the initiator 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane (DBPH) was dissolved in 200 mL of DMF and added dropwise to the reaction vessel over 1.5 hours using a constant-pressure dropping funnel. After the addition was complete, the reaction was continued at 95 °C for 7 hours.
[0046] After the reaction was completed, the heating was stopped and the reaction solution was cooled to room temperature. The product in the kettle was slowly poured into 100 L of deionized water, and a large amount of white solid was precipitated. The solid product was collected by suction filtration and washed with deionized water and ethanol for 4 times in turn. The washed product was placed in a vacuum oven and dried at 85°C for 24 hours under vacuum to obtain functionalized ethylene-tetrafluoroethylene copolymer powder for standby.
[0047] Please refer to the attached Figure 1 :
[0048] Examples 1-3:
[0049] Example 1:
[0050] Raw material components (by mass fraction):
[0051] Functionalized ethylene-tetrafluoroethylene copolymer (f-ETFE): 50;
[0052] Vinyl-terminated polydimethylsiloxane (PDMS-Vi): 30;
[0053] Hydrogen-containing silicone oil: 1.5;
[0054] Microwave-sensitive platinum-palladium catalyst inhibitor: 0.05;
[0055] Infrared-sensitive organic peroxide (DCP): 1.0;
[0056] Fluorine-containing silane coupling agent: 0.5.
[0057] Preparation steps:
[0058] S1, cable core preparation: 19 strands of copper wire with a diameter of 0.18 mm are twisted into a conductor layer; using an extruder, meltable polytetrafluoroethylene (PFA) is coated on the outer periphery of the conductor layer at an extrusion temperature of 400°C to form a fluoroplastic insulation layer; on the outer periphery of the fluoroplastic insulation layer, a layer of copper tape is woven to form a shielding layer; on the outer periphery of the shielding layer, a layer of stainless steel wire is woven to form an armor layer, obtaining a cable core to be coated with a sheath.
[0059] S2, sheath premix preparation: 50 parts of f-ETFE, 30 parts of PDMS-Vi, 1.5 parts of hydrogen-containing silicone oil and 0.5 parts of fluorine-containing silane coupling agent are added into a twin-screw extruder, and the temperature of the melt blending zone of the extruder is set to 130°C for blending. At the end of the blending, 0.05 parts of microwave-sensitive platinum-palladium catalyst inhibitor and 1.0 parts of DCP are added through the side feeding port of the extruder, and the temperature of this region is controlled at 115°C. After the material is rapidly dispersed, it is extruded from the head, cooled and pelletized to obtain sheath premix particles.
[0060] S3, Jacket extrusion: The jacket premix particles prepared in step (S2) are fed into an extruder to coat the armored layer prepared in step (S1). The temperature of the extruder is set as follows: 130°C for the feeding zone, 150°C for the compression zone, and 160°C for the head.
[0061] S4, Energy field gradient crosslinking and post-treatment: The cable coated with uncrosslinked jacket layer is continuously passed through an energy field gradient response vulcanization pipeline at a speed of 5 m / min. First, it passes through a first zone (microwave activation zone) with a microwave field of 2.45 GHz and a power of 20 kW; then it passes through a second zone (infrared curing zone) with infrared rays of a wavelength peak of 3-8 μm and a total power of 80 kW. After leaving the vulcanization pipeline, the cable enters a circulating water tank with a water temperature of 30°C for cooling and shaping, and is wound to obtain the finished cable.
[0062] Example 2:
[0063] Raw material components (by mass fraction):
[0064] Functionalized ethylene-tetrafluoroethylene copolymer (f-ETFE): 60;
[0065] Vinyl-terminated polydimethylsiloxane (PDMS-Vi): 40;
[0066] Hydrogen-containing silicone oil: 2.2;
[0067] Microwave-sensitive platinum catalyst inhibitor: 0.12;
[0068] Infrared-sensitive organic peroxide (DCP): 1.7;
[0069] Fluorine-containing silane coupling agent: 1.2.
[0070] Preparation steps:
[0071] S1, Core preparation: 19 copper wires with a diameter of 0.18 mm are twisted into a conductor layer; a fusible polytetrafluoroethylene (PFA) is used to coat the outer periphery of the conductor layer at an extrusion temperature of 400°C to form a fluoroplastic insulation layer; a copper tape is woven around the outer periphery of the fluoroplastic insulation layer to form a shielding layer; a layer of stainless steel wire is woven around the outer periphery of the shielding layer to form an armored layer, thereby obtaining a cable core to be coated with a jacket.
[0072] S2, Sheath premix preparation: 50 parts of f-ETFE, 30 parts of PDMS-Vi, 1.5 parts of hydrogen-containing silicone oil and 0.5 parts of fluorine-containing silane coupling agent were added into a twin-screw extruder, and the temperature of the melt blending zone of the extruder was set to 130°C for blending. At the end of the blending, 0.05 parts of microwave-sensitive platinum catalyst inhibitor and 1.0 parts of DCP were added through the side feeding port of the extruder, and the temperature of this region was controlled at 115°C. After rapid dispersion, the material was extruded from the die head, cooled and pelletized to obtain sheath premix particles.
[0073] S3, Sheath extrusion: the sheath premix particles prepared in step (S2) were added into an extruder to coat the armor layer of the cable core prepared in step (S1). The temperature of the extruder for sheath extrusion was set as follows: feeding zone 135°C, compression zone 155°C, and die head 165°C.
[0074] S4, Energy field gradient crosslinking and post-processing: the cable running speed was 10 m / min, the microwave power of the first zone was 30 kW, the total infrared radiation power of the second zone was 100 kW, and the water temperature of the cooling water tank was 35°C.
[0075] Example 3:
[0076] Raw material components (by mass fraction):
[0077] Functionalized ethylene-tetrafluoroethylene copolymer (f-ETFE): 70;
[0078] Vinyl-terminated polydimethylsiloxane (PDMS-Vi): 50;
[0079] Hydrogen-containing silicone oil: 3.0;
[0080] Microwave-sensitive platinum catalyst inhibitor: 0.2;
[0081] Infrared-sensitive organic peroxide (DCP): 2.5;
[0082] Fluorine-containing silane coupling agent: 2.0.
[0083] Preparation steps:
[0084] S1, Cable core preparation: 19 strands of copper wire with a diameter of 0.18 mm were twisted into a conductor layer; a meltable polytetrafluoroethylene (PFA) was used to coat the outer periphery of the conductor layer at an extrusion temperature of 410°C using an extruder to form a fluoroplastic insulation layer; a layer of copper tape was woven around the outer periphery of the fluoroplastic insulation layer to form a shielding layer; a layer of stainless steel wire was woven around the outer periphery of the shielding layer to form an armor layer, thereby obtaining a cable core to be coated with a sheath.
[0085] S2, Sheath premix preparation: 50 parts of f-ETFE, 30 parts of PDMS-Vi, 1.5 parts of hydrogen-containing silicone oil and 0.5 parts of fluorine-containing silane coupling agent were added into a twin-screw extruder, and the temperature of the melt blending zone of the extruder was set to 130°C for blending. At the end of the blending, 0.05 parts of a microwave-sensitive platinum catalyst inhibitor and 1.0 parts of DCP were added through the side feeding port of the extruder, and the temperature of this region was controlled at 115°C. After rapid dispersion, the material was extruded from the die head, cooled and pelletized to obtain sheath premix particles.
[0086] S3, Sheath extrusion: the sheath premix particles prepared in step (S2) were added into an extruder to coat the armor layer of the core prepared in step (S1). The temperature of the extruder was set as follows: feeding zone 140°C, compression zone 160°C, and die head 170°C.
[0087] S4, Energy field gradient crosslinking and post-processing: the cable coated with uncrosslinked sheath layer was continuously passed through an energy field gradient response vulcanization pipeline at a speed of 15 m / min. First, it passed through the first zone (microwave activation zone), and a microwave field with a frequency of 2.45 GHz and a power of 40 kW was applied; then it passed through the second zone (infrared curing zone), and an infrared ray with a wavelength peak of 3-8 μm and a total radiation power of 120 kW was applied. After leaving the vulcanization pipeline, the cable entered a circulating water tank with a water temperature of 40°C for cooling and shaping, and the finished cable was wound up.
[0088] Comparative Examples 1-3:
[0089] Comparative Example 1:
[0090] Compared with Example 1, the difference is that in the sheath layer formula, 50 parts of unfunctionalized ethylene-tetrafluoroethylene copolymer (ETFE) is used instead of functionalized ethylene-tetrafluoroethylene copolymer (f-ETFE), and the remaining components and preparation steps are the same.
[0091] Comparative Example 2:
[0092] Compared with Example 1, the difference is that in the sheath layer formula, no fluorine-containing silane coupling agent is added, and the remaining components and preparation steps are the same.
[0093] Comparative Example 3:
[0094] Compared with Example 1, the difference is that in the energy field gradient crosslinking of step (S4), instead of using a two-zone pipeline with microwave and infrared, the cable is passed through a single hot air circulation vulcanization pipeline with a temperature set to 200°C at a speed of 5 m / min, and the remaining components and preparation steps are the same.
[0095] Experiments 1-3:
[0096] Experiment 1:
[0097] Purpose of the experiment: determination of tensile strength and elongation at break of cable sheath.
[0098] Experimental procedure:
[0099] According to the national standard GB / T1040.2-2006. The specific operation steps are as follows:
[0100] Sample preparation: peel the sheath layer from each cable sample, and use a cutting knife to cut a dumbbell-shaped 5A sample.
[0101] Test equipment: use a universal material testing machine, set the test rate to 100 mm / min.
[0102] Test process: clamp the two ends of the sample on the clamps of the testing machine, start the testing machine for stretching until the sample breaks. Record the maximum force value and the change in distance between the marks when the sample breaks.
[0103] Data calculation: calculate the tensile strength (MPa) according to the recorded force value and the initial cross-sectional area of the sample, and calculate the elongation at break (%) according to the recorded change in distance between the marks and the initial distance between the marks. Test 5 valid data for each group of samples, and take the arithmetic mean value.
[0104] The experimental results are shown in Table 1.
[0105] Table 1
[0106] Sample Tensile strength (MPa) Elongation at break (%) Example 1 21.3 458 Example 2 23.8 492 Example 3 25.1 515 Comparative Example 1 10.7 213 Comparative Example 2 14.2 288 Comparative Example 3 12.5 241
[0107] From Table 1, it can be seen that the tensile strength and elongation at break values of the sheath materials of Examples 1-3 are improved compared to those of Comparative Examples 1-3. This indicates that the technical solution provided by the present application provides necessary active sites for subsequent peroxide crosslinking reaction by introducing functional groups on the molecular chain of ethylene-tetrafluoroethylene copolymer, which promotes the effective formation of the first polymer network. The fluoropolymer network and the second organosilicon polymer network formed by platinum catalytic addition reaction together form an interpenetrating polymer network structure inside the material. This structure enables the physical properties of the two networks to be combined, thereby achieving higher mechanical strength and ductility.
[0108] Comparative Example 1 does not use functionalized ethylene-tetrafluoroethylene copolymer, and the crosslinking degree of the fluoropolymer is low, resulting in an incomplete network structure and low tensile strength and elongation at break values. Comparative Example 2 does not contain a fluorine-containing silane coupling agent, which weakens the interface bonding between the fluoropolymer network and the organosilicon network, and the interface is prone to separation under external force, thereby reducing the overall mechanical properties of the material.
[0109] Comparative Example 3 used a single hot air circulation vulcanization process, high temperature simultaneously initiated two crosslinking reactions, platinum gold catalyst activity may be affected by the decomposition of peroxide products and reduce, resulting in the formation of two polymer network process interference with each other, unable to form a neat interpenetrating network structure. Therefore, the mechanical properties of the material values are lower than the example samples prepared by the energy field gradient crosslinking method of the present application. The energy field gradient crosslinking method by the sequential application of microwave and infrared energy field, two crosslinking reactions step by step, fixed point, to ensure the integrity of the respective network structure, so as to obtain the preset material performance.
[0110] Experiment 2:
[0111] Experimental purpose: the finished cable prepared by example 1-3 and comparative example 1-3 is subjected to low temperature bending test.
[0112] Experimental steps:
[0113] According to the national standard GB / T2951.14-2008. The specific operation steps are as follows:
[0114] Sample preparation: cut the sample with a length of not less than 300mm from each finished cable.
[0115] Equipment preparation: prepare a low temperature test box, and a test rod with a diameter of 4 times the outer diameter of the measured cable.
[0116] Test process: put the cable sample and test rod together in the low temperature test box at-40℃ for 4 hours. After taking out the sample from the test box, wind it tightly around the test rod cooled in the low temperature box for 3 turns within 1 minute.
[0117] Result observation: take the wound sample off the test rod, after recovering to room temperature, check whether there is any form of cracking on the surface of the sheath under normal vision.
[0118] Experimental results are shown in Table 2.
[0119] Table 2
[0120]
[0121]
[0122] From Table 2, the cable prepared in Examples 1-3 did not show any cracking on the surface of the sheath after bending at low temperature of -40℃, while the cable sheath of Comparative Examples 1-3 showed different degrees of cracking or breaking. This result shows that the sheath material prepared by the technical scheme of the present application has flexibility at low temperature. This performance is due to the interpenetrating polymer network structure formed inside the material, in which the silicone network formed by crosslinking of end-vinyl polydimethylsiloxane and hydrogen-containing silicone oil can still maintain the movement ability of the polymer chain segment at low temperature, thereby giving the whole material system bending flexibility at low temperature.
[0123] Comparative Example 1 failed to form an effective fluoropolymer crosslinking network due to the use of non-functionalized ethylene-tetrafluoroethylene copolymer, and the material was essentially a physical blend with poor compatibility, and the rigid fluoroplastic matrix broke at low temperature. In Comparative Example 2, no fluorine-containing silane coupling agent was added, resulting in insufficient interfacial bonding force between the fluoropolymer network and the silicone network, and under the action of low-temperature bending stress, peeling occurred at the interface of the two phases, thereby causing the generation and expansion of microcracks.
[0124] Comparative Example 3 used a single high-temperature heating method for crosslinking, and the two crosslinking reaction systems were simultaneously carried out and interfered with each other, resulting in insufficient crosslinking of the silicone network and failure to form a complete flexible network structure to resist low-temperature brittleness. The preparation method of the present application uses energy field gradient crosslinking, and uses the different response characteristics of microwave field and infrared field to realize the step-by-step and sequential formation of the two networks, ensuring the structural integrity of the flexible silicone network, which is the premise for the flexibility of the sample in Example at low temperature.
[0125] Experiment 3:
[0126] Purpose of the experiment: to evaluate the heat aging performance of the cable sheath prepared in Examples 1-3 and Comparative Examples 1-3.
[0127] Experimental steps:
[0128] According to the national standard GB / T2951.12-2008. The specific operation steps are as follows:
[0129] Sample preparation: peel the sheath layer from each cable sample, and use a cutting knife to cut a dumbbell-shaped 5A sample.
[0130] Initial performance test: take part of the sample, and measure the tensile strength and elongation at break before aging according to the method described in Test 1.
[0131] Heat aging treatment: hang the remaining sample in a forced air oven at a temperature of 260℃ for 168 hours.
[0132] Post-aging performance test: the post-aging sample was taken out from the oven and placed at room temperature for at least 16 hours for state conditioning. Subsequently, the post-aging tensile strength and elongation at break were determined according to the method described in Test 1.
[0133] Data calculation: the ratio of post-aging tensile strength to pre-aging tensile strength, and the ratio of post-aging elongation at break to pre-aging elongation at break were calculated respectively, and the results were expressed in percentage (%), i.e. the performance retention rate.
[0134] The experimental results are shown in Table 3.
[0135] Table 3
[0136]
[0137] As shown in Table 3, the sheath materials of Examples 1-3 exhibited high retention rates of tensile strength and elongation at break under high-temperature aging conditions at 260℃. This is because an interpenetrating polymer network composed of cross-linked functionalized ethylene-tetrafluoroethylene copolymer and cross-linked silicone polymer is formed inside the material. Among them, the three-dimensional network structure of fluoropolymer formed by chemical bonding provides a structural basis for the material to resist high-temperature thermal oxidative degradation. At the same time, the physically entangled silicone network restricts the movement of molecular chains at high temperatures, further inhibiting the decline of material performance.
[0138] The sheath material of Comparative Example 1 had the lowest performance retention rate value. The reason is that the ethylene-tetrafluoroethylene copolymer used was not functionalized, and could not be effectively cross-linked under the peroxide system, and a stable fluoropolymer network was not formed, so severe molecular chain rupture occurred at high temperatures. In Comparative Example 2, no fluorine-containing silane coupling agent was added, resulting in insufficient interfacial bonding force between the fluoropolymer phase and the silicone phase. Under the action of thermal stress, separation easily occurs at the interface between the two phases, accelerating the deterioration of the overall performance of the material, so its performance retention rate is lower than that of the examples.
[0139] The sheath material of Comparative Example 3 was cross-linked using a single hot air heating method, and its performance retention rate was also lower than that of the examples. Under this process condition, the platinum catalyst and the organic peroxide are activated at the same time, and the two chemical reaction systems interfere with each other, resulting in insufficient cross-linking of both the fluoropolymer network and the silicone network, and the overall network structure formed has defects, so the thermal stability is reduced. The energy field gradient cross-linking method used in the present application ensures the complete formation of the two network structures by sequentially activating the two cross-linking reactions through the microwave field and the infrared field, which is the structural prerequisite for the material to obtain high thermal aging stability.
Claims
1. A fluoroplastic insulated high temperature resistant fire resistant cable, characterized in that, The cable comprises a conductor layer twisted by multiple copper wires, a fluoroplastic insulation layer coated on the outer periphery of the conductor layer, a shielding layer coated on the outer periphery of the fluoroplastic insulation layer, the shielding layer being a copper braid structure, an armor layer coated on the outer periphery of the shielding layer, the armor layer being woven by stainless steel wires, a sheath layer coated on the outer periphery of the armor layer, the sheath layer comprising the following components in mass fractions: functional ethylene-tetrafluoroethylene copolymer: 50-70 parts by mass; vinyl-terminated polydimethylsiloxane: 30-50 parts by mass; hydrogen-containing silicone oil: 1.5-3.0 parts by mass; energy field gradient responsive synergistic catalysis / crosslinking system: 2.05-2.7 parts by mass; fluorine-containing silane coupling agent: 0.5-2.0 parts by mass.
2. The fluoroplastic insulated high temperature resistant fire resistant cable according to claim 1, characterized in that, The functional ethylene-tetrafluoroethylene copolymer is a graft copolymer of ethylene-tetrafluoroethylene copolymer and 4-hydroxystyrene.
3. The fluoroplastic insulated high temperature resistant fire resistant cable according to claim 1, characterized in that, The energy field gradient responsive synergistic catalysis / crosslinking system is composed of a microwave-sensitive platinum-gold catalyst inhibitor and an infrared-sensitive organic peroxide; the mass fraction of the microwave-sensitive platinum-gold catalyst inhibitor is 0.05-0.2 parts; the mass fraction of the infrared-sensitive organic peroxide is 1.0-2.5 parts.
4. The fluoroplastic insulated high temperature resistant fire resistant cable according to claim 1, characterized in that, The kinematic viscosity of the end-vinyl polydimethylsiloxane at 25°C is 30,000-60,000 mm 2 / s, and the vinyl content is 0.04-0.08 mmol / g.
5. A process for the preparation of a fluoroplastic insulated high temperature resistant fire resistant cable for the preparation of a fluoroplastic insulated high temperature resistant fire resistant cable according to any one of claims 1 to 4, characterized in that, The method comprises the following steps: S1, preparing a cable core: twisting multiple copper wires into a conductor layer, coating a fluoroplastic insulation layer, a shielding layer and an armor layer on the outer periphery of the conductor layer in sequence to obtain a cable core to be coated with a sheath; the shielding layer is formed by braiding a copper tape on the outer periphery of the fluoroplastic insulation layer, and the armor layer is formed by braiding stainless steel wires on the outer periphery of the shielding layer; S2, preparing a sheath premix: blending and granulating functional ethylene-tetrafluoroethylene copolymer, vinyl-terminated polydimethylsiloxane, hydrogen-containing silicone oil, energy field gradient responsive synergistic catalysis / crosslinking system and fluorine-containing silane coupling agent to obtain sheath premix granules; S3, sheath extrusion: extruding the sheath premix granules on the armor layer of the cable core to form an uncrosslinked sheath layer; S4, energy field gradient crosslinking: continuously passing the cable coated with the uncrosslinked sheath layer through an energy field gradient responsive vulcanization pipeline, and crosslinking and curing in the first zone and the second zone in sequence in the pipeline; the first zone is a microwave activation zone, a microwave field with a frequency of 2.45 GHz±50 MHz is applied, and the power is 20-40 kW; the second zone is an infrared curing zone, an infrared ray with a wavelength peak of 3-8 μm is applied, and the total radiation power is 80-120 kW.
6. The method for preparing the fluoroplastic insulated high temperature resistant fireproof cable according to claim 5, characterized in that, In step S2, the preparation of the sheath premix comprises: melt blending the functional ethylene-tetrafluoroethylene copolymer, vinyl-terminated polydimethylsiloxane, hydrogen-containing silicone oil and fluorine-containing silane coupling agent at a temperature of 110-150℃ through a twin-screw extruder; at the end of blending, the energy field gradient responsive synergistic catalysis / crosslinking system is added through the side feeding port of the twin-screw extruder, and is rapidly dispersed at a temperature of 110-120℃ before discharging and granulating.
7. The method for preparing the fluoroplastic insulated high temperature resistant fireproof cable according to claim 5, characterized in that, In step S3, the process parameters of the sheath extrusion are: 120-140℃ in the feeding zone, 140-160℃ in the compression zone, and 150-170℃ in the die head.
8. The method for preparing a fluoroplastic insulated high temperature resistant fireproof cable according to claim 5, characterized in that, In step S4, the continuous passing through an energy field gradient response vulcanization pipeline comprises: The control cable is run at a speed of 5-15 m / min; After the cable leaves the energy field gradient response vulcanization pipeline, it is sent into a circulating water tank for cooling and setting, and the water temperature of the circulating water tank is controlled at 20-40℃.
9. The method for preparing the fluoroplastic insulated high temperature resistant fireproof cable according to claim 5, characterized in that, In step S1, the fluoroplastic insulation layer is a melt polytetrafluoroethylene insulation layer formed by coating at an extrusion temperature of 390-410℃.
Citation Information
Patent Citations
Fluoroplastic fireproof power cable
CN117497232A
Fluoroplastic insulating high-temperature-resistant control cable
CN203444816U
Cited By
Dynamic stable shielding signal cable and preparation method thereof
CN122000128A
A dynamically stable shielded signal cable and its preparation method
CN122000128B